Physicochemical and Aerosolization Assessment of Inhalable Spray Dried Fluconazole Powder - Hamed Hamishehkar; Maryam Pourtahmaseb; Afshin Babazadeh; Shohreh Alipour (Tabriz University of Medical Sciences, 2018)
Background: Respiratory fungal diseases therapy is still facing challenges as a result of increasing autoimmune disorders, cancers, and immunosuppressive medication usage. Fluconazole is a wide spectrum antifungal agent and is still used successfully in the treatment of opportunistic infections in combination with other antifungal agents. Since, the treatment of respiratory fungal diseases requires prolonged hospitalization; it may increase the chances of other opportunistic infections. Considering the reported drug resistance and adverse effects of systemic administration, it appears that localized pulmonary antifungal therapy may be a suitable alternative route. According to the reported suitable inhalation properties of spray dried powders; spray drying technique was used to prepare fluconazole powders. Methods: Different spray drying parameters such as inlet temperature, pump rate, aspiration%, solvent type, as well as fluconazole concentration were evaluated for powder production. The optimized formulations were characterized using scanning electron microscopy (SEM), x-ray diffraction (XRD), differential scanning calorimetry (DSC) and aerodynamic parameters. Results: All selected formulations showed a smooth surface with similar mass median aerodynamic diameter (MMAD) in a respiratory acceptable range. While optimized powder showed a lower geometric standard deviation (GSD) of 1.5 with higher fine particle fraction (FPF) of 26% and almost complete deposition recovery of 97%. Conclusion: Based on in vitro characterization results, it appears that spray drying is an appropriate and cost-effective technique for the production of inhalable fluconazole powder. It is characterized by a narrower size distribution and delivers a higher dose which may be more cost effective for mass production.